Feasibility and agreement of including anterior‐posterior complexes and landmarks of the proximal hemisphere into basic examination of the fetal brain: A prospective study. (2nd March 2020) - Hormazabal, Lorena; Correa, Flavia; Escribano, David; Quiroz, Gabriel; Saint‐Jean, Constanza; Espinel, Andrea; Diaz, Linder; Zambrano, Belkys; Galindo, Alberto; Viñals, Fernando
Abstract: Objective: To assess the feasibility of identifying structures included in anterior complex (AC) and posterior complex (PC), as well as a series of anatomic landmarks that could help to demonstrate the integrity of the cerebral proximal hemisphere (PH). Methods: This was a prospective observational multicenter study of healthy pregnant women attending routine ultrasound screening at 20 + 0 to 33 + 6 weeks' gestation. Six physicians performed transabdominal (TA) ultrasound, in order to obtain the planes required to visualize the AC, PC, and PH. Blind analysis by a nonexpert and two experts in fetal neurosonography was used to assess the structures included in each plane view. Results: In the population studied (n = 747), detection of the structure rates for AC, PC, and proximal hemisphere was of 94%, 93%, and 96%, respectively, with an agreement of 97%, 94%, and 98% when comparing an expert and a nonexpert in fetal brain examiner. Detection of structures in the proximal hemisphere was significantly higher when observed through the proximal hemisphere plane rather than the transventricular plane. Conclusion: Our results suggest that inclusion of AC and PC complexes visualization, as well as real‐time access to the proximal hemisphere, is feasible and could improve the prenatal detection of fetal cerebral anomalies.